Wellbeing Conceptualizations in Family Medicine Trainees: A Hermeneutic Review. Issue 1 (20th January 2022) - Prentice, Shaun; Benson, Jill; Dorstyn, Diana; Elliott, Taryn
Abstract: Phenomenon: High levels of burnout have been widely reported among postgraduate medical trainees, however relatively little literature has examined what 'wellbeing' means for this group. Moreover, the literature that does exist has generally overlooked the potential role of specialty factors in influencing such conceptualizations. This is particularly true for family medicine and general practice trainees – a specialty considered to be unique due, in part, to its focus on community-based care. The present review sought to explore conceptualizations of wellbeing specifically within the context of family medicine and general practice training. Approach: The Embase, Ovid Medline, and PsycINFO databases were searched from inception to November 2019 for literature examining wellbeing in family medicine and general practice trainees. Literature was iteratively thematically analyzed through the process of a hermeneutic cycle. In total, 36 articles were reviewed over seven rounds, at which point saturation was reached. Findings: The findings confirm the complex and multifaceted nature of wellbeing as experienced by family medicine and general practice trainees. An emphasis on psychological factors – including emotional intelligence, positive mental health, self-confidence and resilience – alongside positive interpersonal relationships, rewards, and balanced interactions between trainees' personal and professional demands were deemed critical elements. Insights: A model of wellbeing that emphasizes rich connections between trainees' personal and professional life domains is proposed. Further qualitative research will help to extend current understanding of wellbeing among medical trainees, including the individuality of each specialty's experiences, with the potential to enhance interventional efforts.